Hedge Fund Boards and the Market for Independent Directors - Clifford, Christopher P.; Ellis, Jesse A.; Gerken, William C. (Journal of Financial and Quantitative Analysis, 2018)
We provide the first examination of hedge fund boards and their directors. The majority of directorships are held by extremely busy independent directors. These directors are sought by funds because they have more reputational capital at stake, making them independent and credible monitors whose presence can certify fund quality to investors. Busy independent directors are more likely to be hired by high-quality funds, and their departure from the board is associated with investor withdrawals. Moreover, funds with busy independent directors are less likely to commit fraud, abuse discretionary liquidity restrictions, or engage in performance-based risk shifting.